Frequency‐dependent neural activity in Parkinson's disease - Hou, Yanan (Hum Brain Mapp, 2014)
The brainstem and basal ganglia are important in the pathophysiology of Parkinson's disease (PD). Reliable and sensitive detection of neural activity changes in these regions should be helpful in scientific and clinical research on PD. In this study, we used resting state functional MRI and amplitude of low frequency fluctuation (ALFF) methods to examine spontaneous neural activity in 109 patients with PD. We examined activity in two frequency bands, slow‐4 (between 0.027 and 0.073 Hz) and slow‐5 (0.010–0.027 Hz). Patients had decreased ALFF in the striatum and increased ALFF in the midbrain, and changes were more significant in slow‐4. Additionally, changes in slow‐4 in both basal ganglia and midbrain correlated with the severity of the parkinsonism. The ALFF in the caudate nucleus positively correlated with the dose of levodopa, while the ALFF in the putamen negatively correlated with the disease duration in both slow‐4 and slow‐5 bands. In addition, the ALFF in the rostral supplementary motor area negatively correlated with bradykinesia subscale scores. Our findings show that with a large cohort of patients and distinguishing frequency bands, neural modulations in the brainstem and striatum in PD can be detected and may have clinical relevance. The physiological interpretation of these changes needs to be determined. Hum Brain Mapp 35:5815–5833, 2014. © 2014 Wiley Periodicals, Inc.